2015
DOI: 10.15341/jbe(2155-7950)/01.06.2015/016
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Academics’ Knowledge Sharing Behaviour in United Arab Emirates

Abstract: This study aims to provide an understanding of knowledge sharing behavior among academics in United Arab Emirates universities and assess the factors influencing it. It also identifies the effect of the type of university on academics' knowledge sharing behavior. The study used Ajzen's amended Theory of Planned Behavior to test the research model. Adopting a quantitative research that employed a cross-sectional online survey, data were collected from 105 academics in public and private universities using a que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 39 publications
(65 reference statements)
2
21
0
1
Order By: Relevance
“…Skaik and Othman (2015) in giving an empirical and theoretical background to their study on KSB, note that attitude determines the individual’s intention to actually perform KSB. Shook and Bratianu (2010) state that attitude is formed based on one’s beliefs in the possible outcomes.…”
Section: Conceptualization and Hypotheses Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Skaik and Othman (2015) in giving an empirical and theoretical background to their study on KSB, note that attitude determines the individual’s intention to actually perform KSB. Shook and Bratianu (2010) state that attitude is formed based on one’s beliefs in the possible outcomes.…”
Section: Conceptualization and Hypotheses Generationmentioning
confidence: 99%
“…Several studies have shown a positive relationship between attitude and KSI (Chen et al, 2009; Kuang et al, 2012; Ramayah, 2009; Skaik and Othman, 2015). Attitude towards behaviour for this study will be measured using self-efficacy and extrinsic reward system.…”
Section: Conceptualization and Hypotheses Generationmentioning
confidence: 99%
“…It can be defined as the belief in one's abilities to enhance work productivity and organisational performance. Previous studies suggested that individuals with high self-efficacy and great confidence to contribute their knowledge are more likely to have positive attitudes toward using web tools for knowledge sharing [1], [23]. According to UTAUT model, outcome expectancy was found to be the strongest determinants of sharing knowledge behaviour.…”
Section: Motivationmentioning
confidence: 87%
“…Realizing the importance of knowledge as a significant element in organizations makes creating a competitive climate and enhancing individual and organizational assets allowable. Organizations are seeking different strategies to capture the knowledge and expertise of their human capital by offering incentives to encourage individuals to share their possessed knowledge [42].…”
Section: Discussionmentioning
confidence: 99%
“…Practicing knowledge sharing results in improved organizational effectiveness [43] such as creating new knowledge, innovating, improving performance [43], achieving long term sustainability and success [34], and accelerating individuals' learning [37]. Regardless of the business an organization is engaged in, the type of services or products it is providing, effective knowledge sharing practices are the key to all successful organizations aiming to achieve their objectives [42]. More studies in knowledge sharing are expected to help decision and policy makers in organization in Arab world with a reason to support implementing knowledge sharing strategies.…”
Section: Discussionmentioning
confidence: 99%